An automated control logic generation method for plant sequential-control - Ie, S.; Yamada, N.; Shinbori, T. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
This paper introduces a method for automated generation of control logic. The method helps engineers design software for programmable controllers (PCs) used in plant-control systems. In this method, sequential control logic is generated in the form of a sequential function chart based on functional specifications of the target plant which are represented as keywords. The logic generation process is composed of three steps: converting control specifications into machine states, including initial and final states; searching for a transition path between the initial and final states; and converting state transitions into device operations. The applicability of the proposed method was confirmed through a case study of plant control logic design. Correct control logic was generated for the test cases. The new method needed the input of fewer data than the current design method.